2021
DOI: 10.1080/19475683.2020.1871406
|View full text |Cite
|
Sign up to set email alerts
|

Predicting land use/cover changes and its association to agricultural production on the slopes of Mount Kilimanjaro, Tanzania

Abstract: Increasing demand for food production results in Land use and land cover (LULC) changes, which afflicts the provision of ecosystem services in high mountain areas. This work used time-series LULC and selected spatial metrics to predict the LULC changes for Kikafu-Weruweru-Karanga (KWK) watershed (on the southern slopes of Mt. Kilimanjaro) for the next decade. LULC maps were generated by classifying time-series satellite images. We further predicted the implications for selected staple crop production over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…This study was done at the Kikafu, Weruweru, and Karanga (KWK) watershed, which spans from the thick mountain forest on the southern slopes of Mount Kilimanjaro (Figure 1a). The study area, rainfall pattern (Figure 1b), population and anthropic activities were detailed in Said, Komakech [28] and Said, Hyandye [41]. It is worth mentioning that the largest water extractor is agriculture, being dominated by small to large scale irrigation along the mountain slopes.…”
Section: The Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…This study was done at the Kikafu, Weruweru, and Karanga (KWK) watershed, which spans from the thick mountain forest on the southern slopes of Mount Kilimanjaro (Figure 1a). The study area, rainfall pattern (Figure 1b), population and anthropic activities were detailed in Said, Komakech [28] and Said, Hyandye [41]. It is worth mentioning that the largest water extractor is agriculture, being dominated by small to large scale irrigation along the mountain slopes.…”
Section: The Study Areamentioning
confidence: 99%
“…The assessment results are regarded as acceptable because Kappa values are greater than 80%, as Jensen ( 2007) stated. This procedure is detailed in Said, Hyandye [41]. These maps were independently used to simulate the hydrological impacts of land cover changes at the KWK watershed.…”
Section: Arcswat Model Input Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this conversion at large scales, production is generally fairly low, particularly in rainfed areas (Nakawuka et al, 2018). Similar observations have been reported from irrigation schemes in northern parts of Tanzania, where expansion of farming has reduced native species (Misana et al, 2012;Said et al, 2021). Brockington et al (2008) and Rowcroft (2005) reported that agricultural innovation and technologies have transformed much of the habitats beyond their recovery, and still there is a failure to meet production cost in an effective way.…”
Section: Land Management and Conservation From Local To Regional Scalementioning
confidence: 67%